Pediatric Nasopharyngeal Carcinoma as Seen on 18F-FDG PET/CT - Muzaffar, Razi; Vacca, Francesca; Guo, Huazhang; Mhapsekar, Rishi; Osman, Medhat M. (Frontiers in Oncology, 2019)
Pediatric nasopharyngeal carcinoma is a rare malignancy strongly associated with Epstein-Barr virus infection. Patients typically present with nonspecific symptoms of epistaxis or serous otitis from eustachian tube obstruction and therefore diagnosis is often delayed. We present a case of a previously healthy 17 year old female who initially complained of migraines which was resistant to oral medication. Symptoms progressed and she saw a dental surgeon for concern of a dental infection and was prescribed antibiotics with no relief. Her symptoms continued to progress until ENT visualized a large mass along the floor of the left nasal cavity. Subsequent imaging showed a large mass in the posterior left nasal cavity and biopsy was consistent with nasopharyngeal carcinoma.